Psychodrama Based on Al-Qur'an and Hadith to Improve Students' Emotional Stability - Sholikhah, Linda Dwi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2018)
This conceptual article writing aims to develop science in one of the group counseling techniques that is psychodrama based on Islamic teachings. This conceptual development is based on past research. The existence of the basis of religious teachings are expected to be more understanding and able to instill religious values in adolescents who experience emotional instability. The result of conceptual assessment is psychodrama technique based on Al-Qur'an and Hadith with emphasis on giving verses of Al-Qur'an and Hadith in every treatment. There are 3 steps of psychodrama technique that are (1) warm-up, (2) action, and (3) Sharing and discussion phase with the provision of reinforcement/study of the Verses in the Qur'an and Hadith.